The Role of Market Analysis in Improving Consumer Satisfaction in the E-Commerce and Technology Sector from an Islamic Perspective - Jennatul Ma’wa; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
In today's digital era, the e-commerce and technology sectors are developing rapidly. One of the keys to success in this industry is maintaining consumer satisfaction. Therefore, market analysis becomes a crucial tool for understanding consumer needs and desires. This research aims to examine how market analysis can contribute to enhancing consumer satisfaction in the e-commerce and technology sectors. Using a qualitative approach and secondary data analysis, this article concludes that market analysis can provide deep insights into consumer behavior, market trends, and their preferences, which can ultimately be used to formulate more effective strategies to improve consumer satisfaction.